Investigating Metacognitive Thinking Skills On Problem Solving Related To Social Problems Among Gifted Students In Saudi Arabia - Obaid, Alelyani Salem (2017)
This study examined metacognitive thinking skills on problem solving social problems among gifted students in Saudi Arabia. The results demonstrated the relationships, effects and influence of metacognitive thinking skills for problem solving related to social problems among Saudi Arabian gifted students at different level of study, sub-groups and with respect to gender for the intermediate and secondary schools gifted students. The suggestion and recommendations based on the study findings would benefit the gifted student‘s centers, educational ministry, international and non-governmental organizations in the effort to improve the study learning conditions of gifted students in Saudi Arabia.